The Positive Effects of Self-Regulation Strategy in EFL Reading Dynamics - Wijaya, Kristian Florensio (Universitas Kapuas, 2024)
Amidst complex reading learning enterprises, it is fair to be acknowledged that globalized EFL learners need to improve their reading competencies and activate a self-regulation strategy to experience a positively sound reading learning atmosphere and become more strategic L2 readers knowing the reading strategies working best for their particular reading dynamics. This present small-scale qualitative investigation was conducted with the support of a library study approach to generate more reliable and apprehensible research results beneficial for the betterment of future reading learning dynamics. To achieve this main research objective, the researcher selectively selected 20 previous studies focusing on discovering the positive influences of self-regulation strategy in EFL reading enterprises. Thematic analysis was simultaneously employed while analyzing the previously obtained research results to yield more accurate themes that were rewarding and to pave more meaningful reading pathways for worldwide second language reading instructors and EFL learners. Based on the obtained research results, the internalization of the self-regulation strategy has successfully promoted more enjoyable reading learning processes where they can progressively transform into more autonomous L2 readers. As a point, these specifically attained research results strongly suggested globalized second language reading instructors cultivating EFL learners’ self-regulation growth at the onset of reading learning activities to gradually enable them to become high-achieving L2 readers. Keywords: self-regulation strategy; reading; library study